2023
DOI: 10.1007/s40243-023-00234-7
|View full text |Cite
|
Sign up to set email alerts
|

A review on recent research on bio-based building materials and their applications

S. Bourbia,
H. Kazeoui,
R. Belarbi

Abstract: Bio-based materials represent a promising alternative in building envelope applications, with the aim of improving in-use energy efficiency. They have the advantage of being renewable, low embodied energy and CO2 neutral or negative. In addition, they are excellent thermal regulators. This paper presents an overview of the state-of-the-art of bio-based materials used in building construction and their applications. The materials outlined include hemp, wood, date palm wood, cork, alfa and straw. Through this li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 107 publications
0
6
0
Order By: Relevance
“…However, they may also be more prone to cracking due to their low elasticity modulus and moisture absorption capacity, necessitating specific design and formulation to ensure long-term durability [187]. Environmentally, biomass-based concrete materials offer significant benefits, including plants' ability to absorb carbon dioxide during growth, thereby reducing the overall carbon footprint of constructed structures [188]. These materials also pave the way for new applications in sustainable construction, such as thermal insulation, construction panels, and even structural elements, although challenges remain, including raw material availability and the standardization of formulations to ensure consistent performance [189].…”
Section: Discussionmentioning
confidence: 99%
“…However, they may also be more prone to cracking due to their low elasticity modulus and moisture absorption capacity, necessitating specific design and formulation to ensure long-term durability [187]. Environmentally, biomass-based concrete materials offer significant benefits, including plants' ability to absorb carbon dioxide during growth, thereby reducing the overall carbon footprint of constructed structures [188]. These materials also pave the way for new applications in sustainable construction, such as thermal insulation, construction panels, and even structural elements, although challenges remain, including raw material availability and the standardization of formulations to ensure consistent performance [189].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that the fibrous materials have better thermo-physical properties by virtue of their internal alignment for efficient insulation for thermal transmission [7,9]. The thermal conductivity of straw generally increases with increase in temperature and moisture content, where the change in moisture content is regulated by the vapour transmission properties as well as the inherent porosity.…”
Section: A Strategic Framework For Bioclimatic Assessment Of Agro-bas...mentioning
confidence: 99%
“…In this aspect, the agriculture sector has been contributing significantly to the construction sector by providing a rich source of raw materials and by enabling considerable value addition during recycling. Agro-based building materials are found to be excellent choice because of their low carbon footprint, energy efficiency, alternate positive contribution from wastes, and additional thermal and acoustic features [5][6][7][8][9]. Typically, they are of many kinds based on the plant of origin, physical appearance and intended applications.…”
Section: Introductionmentioning
confidence: 99%
“…Electrical energy is essential in advancing and developing industrialized nations, especially in the 21st century [3]. In buildings, energy and electricity needed for heating and cooling purposes have notably increased from 118 EJ in 2010 to about 128 EJ in 2019 [4]. If these trends continue to prevail, buildings could be considered the world's largest energy utilizers by 2025, consuming more energy than the combination of both transportation and manufacturing sectors.…”
Section: Introductionmentioning
confidence: 99%
“…The given review is a dataset detailing all the sustainable materials that can be integrated into a building layer, lower energy consumption, and act as an insulation material; no similar published research is found and expanded as much. My authors dealt with publications similar in the domain are subsets of this comprehensive review as they only deal with one type of sustainable materials, such as bio-sourced, that are being considered to be implemented in the building industry [4,11,12,16,17]. What is interesting about this study is that the majority of these considered resources for building and insulating purposes are available in the Mediterranean and North African regions.…”
Section: Introductionmentioning
confidence: 99%